2001
DOI: 10.1161/hq0901.094280
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Gene −174G>C and −572G>C Promoter Polymorphisms Are Strong Predictors of Plasma Interleukin-6 Levels After Coronary Artery Bypass Surgery

Abstract: Abstract-Interleukin-6 (IL-6) synthesized in response to diverse stimuli may play an important role in bridging the inflammatory and atherosclerotic processes. The acute-phase response after coronary artery bypass graft surgery (CABG) is associated with the induction and release of cytokines, such as IL-6. We have examined the effect of common polymorphisms in the IL-6 gene promoter (Ϫ174GϾC, Ϫ572GϾC, and Ϫ597GϾA) on IL-6 levels after elective CABG. DNA extracted from the peripheral blood of 127 patients was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
285
5
16

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(327 citation statements)
references
References 55 publications
19
285
5
16
Order By: Relevance
“…The 2174 G/C polymorphism is a common variant that regulates the serum concentration of IL-6 (22-28). In keeping with previous studies in patients with CVD (28), coronary artery bypass grafting surgery (23,25), carotid atherosclerosis (24), abdominal aortic aneurysm (22), and dialysis (26), we found that patients with CKD and CC genotype had higher circulating levels of IL-6 and CRP than those harboring GC or GG genotypes, specifically legitimating the use of this genetic marker as an unbiased means for assessing the causal nature of the link between the gene product (IL-6) of this polymorphism and CV complications in CKD. Interestingly, this analysis showed that this polymorphism is independently associated both with the history of CVD as well as with incident CV events.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The 2174 G/C polymorphism is a common variant that regulates the serum concentration of IL-6 (22-28). In keeping with previous studies in patients with CVD (28), coronary artery bypass grafting surgery (23,25), carotid atherosclerosis (24), abdominal aortic aneurysm (22), and dialysis (26), we found that patients with CKD and CC genotype had higher circulating levels of IL-6 and CRP than those harboring GC or GG genotypes, specifically legitimating the use of this genetic marker as an unbiased means for assessing the causal nature of the link between the gene product (IL-6) of this polymorphism and CV complications in CKD. Interestingly, this analysis showed that this polymorphism is independently associated both with the history of CVD as well as with incident CV events.…”
Section: Discussionsupporting
confidence: 82%
“…Because transmission of genes is a random phenomenon, gene polymorphisms modulating IL-6 synthesis may represent an unbiased means for testing whether the link between IL-6 and CV outcomes in patients with CKD is causal (Mendelian randomization). The 2174 G/C single-nucleotide polymorphism is a functional variant located in the promoter region of the IL-6 gene that regulates the rate of IL-6 gene transcription (22)(23)(24)(25)(26)(27)(28) and therefore represents a reliable research tool for testing the nature (causal versus noncausal) of the link between IL-6 and CV outcomes in CKD. With this background in mind, we set out to confirm findings by Barreto et al (21) in a large observational study with a carefully characterized cohort of 755 patients with stages 2-5 CKD and to test whether this relationship may underlie a causal link by applying the Mendelian randomization approach (i.e., by stratifying the study population according to the functional 2174 G/C polymorphism in the IL-6 gene).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the genes regulating IL-6 homeostasis. Data on the relation between variations in the IL6 gene, which encodes IL-6, and IL-6 levels are conflicting (33)(34)(35). In an earlier analysis of U.S. women, we did not find significant associations between IL6 genetic variability and IL-6 levels (19).…”
Section: Discussioncontrasting
confidence: 75%
“…Fatigued breast cancer survivors also had a higher percentage of homozygous genotypes (G/ G) and (C/C) for the IL-6 -174 promoter polymorphism, and a higher percentage of homozygous (A/A) and heterozygous (G/A) genotypes for the IL-6R -183 polymorphism. Each of these genotypes has been associated with increased expression of their respective cytokine (e.g., Brull et al, 2001;Burzotta et al, 2001;Galicia et al, 2004;di Giovine et al, 1992). We did not find an association between fatigue-related genotypes and circulating cytokine concentrations, possibly due to the small sample size and the relatively low levels of these markers in this otherwise healthy sample; it is possible that differences might have emerged following in vivo immune stimulation, as seen in previous research (e.g., Bennermo et al, 2004).…”
Section: Risk Factors For Inflammation and Fatiguementioning
confidence: 44%